2013
DOI: 10.1016/j.ntt.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes at 5 years in children exposed prenatally to maternal dental amalgam: The Seychelles Child Development Nutrition Study

Abstract: Limited human data are available to assess the association between prenatal mercury vapor (Hg0) exposure from maternal dental amalgam restorations and neurodevelopment of children. We evaluated the association between maternal dental amalgam status during gestation and children’s neurodevelopmental outcomes at 5 years in the Seychelles Child Development Nutrition Study (SCDNS). Maternal amalgam status was determined prospectively in a longitudinal cohort study examining the associations of prenatal exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This has been tested in two birth cohort studies. (i) In the Seychelles, a detailed study showed no effect of the number of amalgams in pregnancy and child motor development at 9 and 30 months or neurodevelopment at age 5 years; there were no adverse associations with educational achievement, language or other cognitive outcomes at 5 years old. (ii) An analysis of the ALSPAC cohort demonstrated no relationship between speech and language development at 15 months and any measure of prenatal DA exposure.…”
Section: Discussionmentioning
confidence: 96%
“…This has been tested in two birth cohort studies. (i) In the Seychelles, a detailed study showed no effect of the number of amalgams in pregnancy and child motor development at 9 and 30 months or neurodevelopment at age 5 years; there were no adverse associations with educational achievement, language or other cognitive outcomes at 5 years old. (ii) An analysis of the ALSPAC cohort demonstrated no relationship between speech and language development at 15 months and any measure of prenatal DA exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Studies on fetal mercury exposure from amalgam fillings have focused on possible effects on neurodevelopment. It is also of interest to include other birth outcomes in studies dealing with prenatal mercury exposure.…”
mentioning
confidence: 99%
“…In both the Seychelles main and follow-up cohorts, no associations were found between maternal amalgam history and expressive or receptive language as measured by the PLS (Watson et al, 2011; Watson et al, 2013). In the follow-up cohort, there was also no association between maternal amalgam history and verbal knowledge as measured by the Kaufman Brief Intelligence Test at 5 years of age (Watson et al, 2013). …”
Section: Mercurymentioning
confidence: 85%
“…The follow-up cohort was established to assess the effects of prenatal MeHg exposure, while controlling for the beneficial influence of a diet high in ocean fish. Researchers have also assessed the association between maternal dental amalgam (which contains a less toxic form of mercury) and neurodevelopmental outcomes in the Seychelles cohorts (Watson et al, 2011; Watson et al, 2012; Watson et al, 2013). Discussed here are results from the Seychelles, Faroe Islands, and other cohort studies that have assessed prenatal MeHg exposure and neurodevelopment.…”
Section: Mercurymentioning
confidence: 99%